2007
DOI: 10.1038/sj.ki.5002044
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus balance and mineral metabolism with 3h daily hemodialysis

Abstract: Poor control of mineral metabolism is independently associated with mortality in patients receiving hemodialysis. We analyzed data from a 12-month, prospective, non-randomized, controlled study of daily hemodialysis (DHD) (six sessions/week 3 h each) (n=26) vs conventional hemodialysis (CHD) (three sessions/week 4 h each) (n=51) for achievement of mineral metabolism goals and we performed a substudy of weekly dialytic phosphorus removal in DHD vs CHD. Phosphorus control was superior in the DHD group (% change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 41 publications
3
54
1
1
Order By: Relevance
“…Therefore, a veritable wall is erected, below which the phosphorus level cannot drop without increasing dialytic removal, unless the patient risks malnutrition. We provide evidence that conventional hemodialysis removes only 1572 mg/wk when the serum phosphorus is well controlled, whereas with similar predialysis phosphorus levels, short daily hemodialysis removes approximately 2452 mg of phosphorus in a week (39). Therefore, at lower levels of predialysis serum phosphorus, conventional hemodialysis has very limited phosphorus removal.…”
Section: Mineral Metabolism: How To Get Control?mentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, a veritable wall is erected, below which the phosphorus level cannot drop without increasing dialytic removal, unless the patient risks malnutrition. We provide evidence that conventional hemodialysis removes only 1572 mg/wk when the serum phosphorus is well controlled, whereas with similar predialysis phosphorus levels, short daily hemodialysis removes approximately 2452 mg of phosphorus in a week (39). Therefore, at lower levels of predialysis serum phosphorus, conventional hemodialysis has very limited phosphorus removal.…”
Section: Mineral Metabolism: How To Get Control?mentioning
confidence: 93%
“…Phosphate efflux then falls off, but remains at roughly half the initial value at the end of the treatment despite stable serum phosphorus levels. Recently, we directly measured serum phosphorus removal in a group of conventional and short daily hemodialysis patients with good control of serum phosphorus (predialysis phosphorus 4.2 to 4.5 mg/dl), and we found that daily dialysis removes significantly more phosphorus than conventional and that conventional dialysis removes only 1573 mg of phosphorus, when predialysis phosphorus levels are well controlled (39). What is clear is that conventional dialysis does not remove sufficient phosphorus to achieve good control of serum phosphorus in the majority of dialysis patients.…”
Section: Phosphorus Removal With Hemodialysis Is Limitedmentioning
confidence: 99%
“…Adult chronic hemodialysis patients at the Texas Diabetes Institute (San Antonio, TX) were enrolled in a 12-month study to assess the effects of hemodialysis on cardiac function (41). Baseline and 12-month transthoracic echocardiograms were performed by using standard techniques and reviewed by two independent cardiologists blinded to the examination date and therapy status.…”
Section: Methodsmentioning
confidence: 99%
“…Long intermittent HD, performed for 8 h during the day, three times per week, has been associated with better BP control and a lower standardized mortality rate (5). Short daily HD, performed for at least 2 h, five to six times per week, may improve phosphate and BP control (6,7). Home nocturnal HD (HNHD), performed for 7 to 8 h, five to seven nights per week, can normalize phosphate levels without need for binders (8), improve BP control with few or no antihypertensive medications (9), restore impaired left ventricular systolic function (10) and vascular function (11,12), improve left ventricular mass (13), and stabilize coronary artery calcification (14).…”
mentioning
confidence: 99%